Android-based Nahdlatut Turots Manuscript Application - Mochammad Irfan Efendi; Dwi Cahyono (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2024)
The digitization of Turots manuscripts by Nahdlatut Turots is an important step in preserving Islamic intellectual heritage, which is vulnerable to deterioration. Turots refers to the works of scholars in fields such as fiqh, tauhid, tasawuf, and Arabic language, often written in Arabic script or Pegon. This research aims to develop an Android-based application to facilitate the digital preservation and management of kitab Turots. The application is designed to improve access to classical books and create opportunities for further research. Through this application, it is expected that the preservation of kitab Turots will be enhanced, accessibility will be increased, and the digital conservation of Nusantara scholars' intellectual heritage will be supported. The system is developed using the System Development Life Cycle (SDLC) with the Rapid Application Development (RAD) model to accelerate the development process while ensuring system quality. The Technology Acceptance Model (TAM) is used to evaluate user acceptance, measuring perceived usefulness, ease of use, and behavioral intention to use. Additionally, Google Cloud computing services are integrated to enhance storage, security, and scalability, ensuring seamless access to digital manuscripts. The system is tested using the black-box testing method to verify functionality.